Hydrodynamic mechanisms of topographic evolution in straight sandy beach: a case study of Wanpingkou beach, China - Li, Kang; Hao, Yi; Wang, Nan; Feng, Yingming; Song, Dehai; Chen, Yanyu; Zhang, Hao; Ren, Zhaopeng; Bao, Xianwen (Frontiers in Marine Science, 2024)
Stricter controls on destructive human activities in recent years have improved the protection and management of sandy coasts in China. Marine-driven geomorphic changes have become the predominant process influencing future beach evolution. However, in the complex geomorphic conditions of mixed artificial and natural coastlines, the mechanisms and contributions of various marine-driven factors to beach changes remain unclear. Using methods of field observations and numerical simulations by FVCOM model, this study reveals the sedimentary dynamic mechanism of straight sandy beach in the southern Shandong Peninsula (Wanpingkou beach, WPK beach). From 2005 to 2016, the northern section of WPK Beach eroded at a rate of approximately 2-3 m/year, the middle section at about 0.5-1.5 m/year, and the southern section accrued at an average rate of about 1-2 m/year, demonstrating an overall pattern of "northern erosion and southern accretion." During winter, the average grain size of beach sediments is about 0.5 mm with minimal variations, indicating an onshore transport trend; in summer, the average grain size is about 0.7 mm with larger variations, indicating an offshore transport trend. Offshore sediment transport correlates mainly with seasonal changes in wind direction, while alongshore sediment transport is influenced by tidal currents, wind-induced currents, and wave-induced currents. Wave-induced currents are the primary force in alongshore sediment transport with a velocity of 0.1-0.3 m/s toward southwest. Followed by tidal currents with a velocity of 0.05-0.1 m/s, and wind-induced currents with a velocity of 0-0.1 m/s, which have a relatively minor impact. Therefore, seasonal changes in beach morphology are primarily controlled by waves, while interannual variations is mainly influenced by a combination of wave-induced currents and tidal currents. With increasing efforts in beach maintenance and coastal ecological restoration in recent years, understanding the sedimentary dynamics of beaches remains of vital theoretical and practical value.